Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s11883-012-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent Findings on the Effects of Marine-Derived n-3 Polyunsaturated Fatty Acids on Urinary Albumin Excretion and Renal Function

Abstract: Albuminuria (this includes microalbuminuria and macroalbuminuria) and reduced glomerular filtration rate are present not only in high-risk populations, but also in the general population. These manifestations of renal disease are associated with an increased risk of cardiovascular disease and may reflect subclinical vascular disease. Long-chain n-3 polyunsaturated fatty acids have been vigorously studied for their potential cardioprotective effects. These fatty acids reduce the levels of serum lipids, blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…The observed inverse association of Omega-3 fatty acids with ACR is concordant with a multitude of well-established beneficial effects of n-3 fatty acids on the cardiovascular system (31). Hypertension, oxidative stress, dyslipidemia, endothelial dysfunction and thrombogenesis are all intermediaries in the pathogenesis of both kidney disorders and cardiovascular disease-and all are positively modifiable through n-3 PUFAs (21,32,33). As already shown earlier by our group, omega-3 fatty acids are inversely associated with blood pressure in the same, mostly normotensive population, which may be a driver for kidney damage in young and healthy individuals (4).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The observed inverse association of Omega-3 fatty acids with ACR is concordant with a multitude of well-established beneficial effects of n-3 fatty acids on the cardiovascular system (31). Hypertension, oxidative stress, dyslipidemia, endothelial dysfunction and thrombogenesis are all intermediaries in the pathogenesis of both kidney disorders and cardiovascular disease-and all are positively modifiable through n-3 PUFAs (21,32,33). As already shown earlier by our group, omega-3 fatty acids are inversely associated with blood pressure in the same, mostly normotensive population, which may be a driver for kidney damage in young and healthy individuals (4).…”
Section: Discussionsupporting
confidence: 61%
“…In CKD treatment, the reduction of albuminuria remains a central pillar. Concerning the effects of n-3 PUFAs, longitudinal, interventional studies focusing on healthy adults with preserved kidney function, where prevention measures could be of particular importance are not available (21). From an interventional perspective, Elajami et al (10) showed, that EPA and DHA supplementation was able to attenuate the progression of established albuminuria in patients with type 2 diabetes mellitus and coronary artery disease, most of whom were already under treatment with angiotensin-converting enzyme inhibitors or angiotensin-receptor blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Omega‐3 polyunsaturated fatty acids are a dietary component that can be obtained in fatty fish or as supplements. Results of prior studies examining the effect of omega‐3 fatty acids on albuminuria have had variable results in nondiabetic and diabetic subjects, but no study has examined their effect on albuminuria in patients with CAD. The objective of the current study was to assess the effect of very long‐chain omega‐3 fatty acids—eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in the form of Lovaza—on albuminuria in patients with stable CAD both with and without type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…While LCω3FA were reported to reduce proteinuria, 42 the impact of fish oil consumption on renal function and ESRD progression remains contradictory. 43 To the best of our knowledge, we show for the first time that long-term fish oil replacement prevents progression to ESRD and cardiovascular dysfunction in a murine model of T2D. We also provide evidence for the potential therapeutic benefits of both DHA-derived resolution mediators; 17-HDHA and PDX on ESRD and associated cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 55%
“…Much less is known about their potential benefits for DN. While LCω3FA were reported to reduce proteinuria, 42 the impact of fish oil consumption on renal function and ESRD progression remains contradictory 43 . To the best of our knowledge, we show for the first time that long‐term fish oil replacement prevents progression to ESRD and cardiovascular dysfunction in a murine model of T2D.…”
Section: Discussionmentioning
confidence: 75%